2020
DOI: 10.3390/catal10101208
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Photocatalytic Performance of Multilayer ZnO for Water Splitting by Biaxial Strain Composites

Abstract: Novel two-dimensional (2D) materials have received extensive attention in the field of photocatalysis due to their unique properties. Traditional ZnO material with wurtzite structure transforms into a stable graphite-like structure that has the characteristics of 2D material when its thickness is less than a few atomic layers. In this work, using first-principles calculations, we investigated the potential of multilayer graphite-like ZnO as a photocatalyst for water splitting. The results showed that multilaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The MO layer possesses a similar bond length in both odd and even layered cases and these results are quite consistent with earlier works. 6,7,45 The critical thickness for stabilizing the WZ slab as well as the 2D-MO slab is also estimated by comparing the energetics of both cases, as shown in Fig. 3.…”
Section: Paper Pccpmentioning
confidence: 99%
“…The MO layer possesses a similar bond length in both odd and even layered cases and these results are quite consistent with earlier works. 6,7,45 The critical thickness for stabilizing the WZ slab as well as the 2D-MO slab is also estimated by comparing the energetics of both cases, as shown in Fig. 3.…”
Section: Paper Pccpmentioning
confidence: 99%
“…Merging the sustainability with durability may be the key of transferring the photocatalytic process from the laboratory scale up to large applications. Until now there are many wide gap oxides (TiO 2 [ 4 , 5 ], SnO 2 [ 6 , 7 ], and ZnO [ 8 , 9 ]) and narrow band gap materials (Bi 2 WO 6 [ 10 , 11 ], Ag 3 PO 4 [ 12 , 13 ], BiPO 4 [ 14 , 15 ], g-C 3 N 4 [ 16 , 17 ], WO 3 [ 18 , 19 ], and BiOX [ 20 , 21 ]) studied for the potocatalytic removal of wastewater organic contaminants and indoor pollutants. The mono-components photocatalyst have disadvantages such as narrow visible light absorption [ 22 , 23 ], low specific surface area [ 24 , 25 ], and fast charge carriers recombination [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the use of photocatalytic water splitting for hydrogen production is an attractive strategy in the field of energy conversion with abundant solar energy, since the pioneering report of photoelectrochemical water splitting was published in 1972 [2]. Currently, a lot of photocatalysts, such as TiO 2 [3][4][5], WO 3 [6,7], g-C 3 N 4 [8][9][10], ZnO [11][12][13], and metal complexes [14][15][16], have been employed for the photocatalytic water splitting reaction. However, it has been demonstrated that most of these photocatalysts with wide band gaps are only active under UV irradiation.…”
Section: Introductionmentioning
confidence: 99%